Competências gerenciais: um estudo em empresas startups brasileiras - Figueira, Kristina Kieling (2016)
In view of the current business scenario the challenge for managers is to find a way of working that enable them to manage the various demands they face, especially those operating in technology startups, where innovation and adaptation to change is constant. The development and improvement of skills and managerial roles can make a difference and support the decisions and strategies outlined. In this way, this study had as objective understand which management skills and roles are developed by managers of Brazilian startups, based in the model of Quinn et al. (2003). The research is characterized as descriptive, quantitative, and as a research method survey was used. The gathering took place through the online questionnaire sent to companies registered in the database of Associação Brasileira de Startups (ABS), obtaining the return of 195 companies concentrated mainly in the Southeast and South of Brazil. The results found pointed that the skills most developed by managers of startups are those inherent in the producer and director roles, demonstrating that the model of the rational goals is the one that guides the management of these companies, focused on productivity and organizational profit. The management profile identified in the results points to the characteristics of an effective leader management, however managers develop the skills of the Competing Values Framework (CVF) at an average level, presenting certain imbalance in the performance of roles.